Control and management in next-generation networks challenges andopportunities. - Modarressi, A.R.
This article discusses the challenges and opportunities associated with a fundamental transformation of current networks toward a multiservice ubiquitous infrastructure with a unified control and management architecture. After articulating the major driving forces for network evolution, we outline the fundamental reasons why neither the control infrastructure of the PSTN nor that of the present-day Internet is adequate to support the myriad of new services in next-generation networks. Although NGN will inherit heavily from both the Internet and the PSTN, its control and management architecture is likely to be radically different from both, and will be anchored on a clean separation between a QoS-enabled transport/network domain and an object-oriented service/application domain, with a distributed processing environment that glues things together and universally addresses issues of distribution, redundancy, and concurrency control for all applications. Finally, we allude to the transition issues and show how voice-over-packet services are emerging as the bootstrap application for marshaling in the NGN architecture
Keywords: Internet; PSTN; QoS-enabled transport/network domain; Bootstrap application; Concurrency control; Control; Control infrastructure; Distributed processing environment; Distribution management; Multiservice ubiquitous infrastructure; Network evolution; Next-generation networks; Object-oriented service/application domain; Redundancy; Voice-over-packet services